2004
DOI: 10.1001/jama.291.18.2221
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the Cyclooxygenase 2 Gene as an Inherited Protective Factor Against Myocardial Infarction and Stroke

Abstract: LTHOUGH MYOCARDIAL INfarction (MI) and atherothrombotic ischemic stroke are thought to be caused by rupture of vulnerable atherosclerotic plaques, 1 they are recognized to be complex disorders that likely result from multifaceted interactions between an in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
179
5
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(198 citation statements)
references
References 28 publications
12
179
5
2
Order By: Relevance
“…However, there is little information available regarding the possible influence of this polymorphism on COX-2 expression and atherosclerosis development in vivo as well as its possible association with reduced risk of cardiovascular events [17]. Recently, C allele has been shown to be associated with reduced risk of myocardial infarction, stroke [18] and a decreased risk of Alzheimer's disease [22]. Moreover, our group has shown that COX-2-dependent PGE 2 release by blood monocytes is related to subclinical atherosclerosis in apparently healthy subjects exposed to cardiovascular risk factors [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is little information available regarding the possible influence of this polymorphism on COX-2 expression and atherosclerosis development in vivo as well as its possible association with reduced risk of cardiovascular events [17]. Recently, C allele has been shown to be associated with reduced risk of myocardial infarction, stroke [18] and a decreased risk of Alzheimer's disease [22]. Moreover, our group has shown that COX-2-dependent PGE 2 release by blood monocytes is related to subclinical atherosclerosis in apparently healthy subjects exposed to cardiovascular risk factors [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Papafili et al have described a common variant in the 5V-flanking region of the COX-2 gene À 765G > C that is associated with lower promoter activity in vitro in the presence of the C allele, and reduced levels of C-reactive protein (CRP), a systemic marker of inflammation, in patients with clinical and subclinical atherosclerosis. This single nucleotide polymorphism (SNP) has also been associated with a reduction in the risk of future clinical cardiovascular events [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…SNPs Biological effect TLR4 (NM-138554.1) +896A/G (Asp299Gly; rs4986790) Determining a single amino acid substitution in the extracellular receptor domain and, hence, a blunted innate/inflammatory response to both foreign pathogens and endogenously generated inflammatory ligands ) PTGS2 (NM-000963) (Cox-2 gene) À765G/C (rs20417) Located within a putative binding site for the transcription factor Sp1, determining a reduction in the expression of Cox-2 enzyme (Cipollone et al, 2004;Orbe et al, 2006) …”
Section: Genesmentioning
confidence: 99%
“…Changes in eicosanoid levels are also correlated with SNPs in the promoter region of PTGS2 and 5-Lo genes, respectively codifying the cyclooxygenase-(Cox)-2 and 5-lipoxygenase (5-Lo), enzymes involved in arachidonic acid metabolism. Two functional (À765G/C PTGS2 and À1708G/A 5-Lo) SNPs have recently been identified and associated with the major age-related diseases (Candore et al, 2007a,b;Caruso et al, 2009;Cipollone et al, 2004;In et al, 1997;Orbe et al, 2006). To clarify and confirm the possible pathophysiological effects of +896A/G TLR4 SNP (Balistreri et al, 2004(Balistreri et al, , 2010, we analysed the levels of IL-6, TNF-a, IL-10 and eicosanoids (LTB4 and PGE2) in LPS-stimulated whole blood samples in vitro of 50 young healthy Sicilians, screened for the presence of +896A/G TLR4 SNP.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the CC and GC genotypes were associated with adverse vascular events and that patients carrying the C allele were more likely to develop AR than those without carriers. Cipollone F et al21 have shown that the incidence of cerebral infarction and myocardial infarction in patients with CC and GC genotypes is relatively low and this may be associated with the reduced risk of ischemic cardiovascular and cerebrovascular disease. In this study, no single nucleotide polymorphisms at ‐765G> C were found to be associated with AR.…”
Section: Discussionmentioning
confidence: 99%